Reinventing character education: the potential for participatory character education using MacIntyre's ethics. Issue 4 (4th July 2022) - Hart, Peter
ABSTRACT: Character Education in the UK is often considered controversial through its perceived neoliberal individualizing of character, disregarding of young people's moral agency, and blindness to the effect of social structures. This article presents an alternative framework for character educators, focussed on the biographical narratives of the students and the practice of teaching. It draws on the work of MacIntyre as a philosophical basis for a participatory form of character development. This perspective provides an answer to perennial criticism of the Character Education field as overly concerned with deficit models and pathologising the effects of social inequality. The article will conclude by calling for a new agenda within the practise of Character Education that is focused in three areas: developing the attributes required to learn well with others, developing the metacognitive skills to function as autonomous ethical agents, and to work with schools to ensure external pressures do not take precedence over the flourishing of students.